Effects of focused electron beam irradiation parameters on direct nanostructure formation on Ag surfaces - Sniķeris, Jānis; Gerbreders, Vjačeslavs; Bulanovs, Andrejs; Sļedevskis, Ēriks (Beilstein Journal of Nanotechnology, 2022)
Metallic nanostructures are applied in many fields, including photonics and plasmonics, due to their ability to absorb or emit light at frequencies which depend on their size and shape. It was recently shown that irradiation by a focused electron beam can promote the growth of nanostructures on metal surfaces and the height of these structures depends on the duration of the irradiation and the material of the surface. However, the effects on growth dynamics of numerous irradiation parameters, such as beam current or angle of incidence, have not yet been studied in detail. We explore the effects of focusing, angle of incidence, and current of the electron beam on the size and shape of the resulting structures on an Ag surface. In addition, we investigate how the nitrogen plasma cleaning procedure of a vacuum chamber can affect the growth of these structures. A beam current of around 40 pA resulted in the fastest structure growth rate. By increasing the beam diameter and angle of incidence the growth rate decreased; however, by raising the beam focus up to 5–6 μm above the surface the growth rate increased. Vacuum chamber cleaning reduced structure growth rate for a few hours. These findings can help to better control and optimise the growth of nanostructures on metal surfaces undergoing irradiation by a focused electron beam.
Keywords: atomic force microscopy; electron beam; lithography; nanostructure; silver; sputtering; surface

(untitled) - Bhushan, B. (Microelectron. Eng., 2007)

(untitled) - Yeom, S.-H.; Kim, O.-G.; Kang, B.-H.; Kim, K.-J.; Yuan, H.; Kwon, D.-H.; Kim, H.-R.; Kang, S.-W. (Opt. Express, 2011)

(untitled) - Lindquist, N. C.; Nagpal, P.; McPeak, K. M.; Norris, D. J.; Oh, S.-H. (Rep. Prog. Phys., 2012)

(untitled) - Soh, H. T.; Quate, C. F.; Morpurgo, A. F.; Marcus, C. M.; Kong, J.; Dai, H. (Appl. Phys. Lett., 1999)

(untitled) - Jung, J.-Y.; Yang, W.-G.; Hong, S.-h.; Kim, G.-H.; Hwang, K.; Chae, W.-S. (Appl. Surf. Sci., 2020)

(untitled) - Samavati, Z.; Samavati, A.; Ismail, A. F.; Rahman, M. A.; Othman, M. H. D.; Yeganeh, F. N. (Opt. Fiber Technol., 2021)

(untitled) - Barman, D.; Saikia, L.; Sarma, B. K. (Mater. Today: Proc., 2022)

(untitled) - Vieu, C.; Carcenac, F.; Pépin, A.; Chen, Y.; Mejias, M.; Lebib, A.; Manin-Ferlazzo, L.; Couraud, L.; Launois, H. (Appl. Surf. Sci., 2000)

(untitled) - van Dorp, W. F.; Hagen, C. W. (J. Appl. Phys., 2008)

(untitled) - Wnuk, J. D.; Rosenberg, S. G.; Gorham, J. M.; van Dorp, W. F.; Hagen, C. W.; Fairbrother, D. H. (Surf. Sci., 2011)

(untitled) - Huth, M.; Porrati, F.; Dobrovolskiy, O. V. (Microelectron. Eng., 2018)

(untitled) - Rykaczewski, K.; Marshall, A.; White, W. B.; Fedorov, A. G. (Ultramicroscopy, 2008)

(untitled) - Luo, J. S.; Sung, C. S.; Hsu, W. S.; Huang, L. Y.; Russell, J. D. (Microelectron. Reliab., 2010)

(untitled) - Liu, H. F.; Li, C. G.; Ansah Antwi, K. K.; Chua, S. J.; Chi, D. Z. (Mater. Lett., 2014)

(untitled) - Zhdanov, G. S.; Manukhova, A. D.; Lozhkin, M. S. (Bull. Russ. Acad. Sci.: Phys., 2014)

(untitled) - Stewart, R. L. (Phys. Rev., 1934)

(untitled) - Bance, U. R.; Drummond, I. W.; Finbow, D.; Harden, E. H.; Kenway, P. (Vacuum, 1978)

(untitled) - Postek, M. T. (Scanning, 2006)

(untitled) - Hirsch, E. H. (Br. J. Appl. Phys., 1960)

(untitled) - Seiler, H. (J. Appl. Phys., 1983)

(untitled) - Wang, D.; Cai, Y.; He, Y.; Xu, Y.; Jia, Q. (Results Phys., 2022)

(untitled) - Hristu, R.; Stanciu, S. G.; Tranca, D. E.; Stanciu, G. A. (Appl. Surf. Sci., 2015)

(untitled) - Orekhova, K. N.; Serov, Yu. M.; Dement’ev, P. A.; Ivanova, E. V.; Kravets, V. A.; Usacheva, V. P.; Zamoryanskaya, M. V. (Tech. Phys., 2019)

(untitled) - Mitchell, D. R. G. (Micron, 2015)

(untitled) - Song, Y.; Lu, Q.; Gong, X.; Wang, D.; Zhang, Z.; Yu, B.; Yao, S.; Mao, Q.; Ma, T.; Bai, Y. (Vacuum, 2022)

(untitled) - Bret, T.; Mauron, S.; Utke, I.; Hoffmann, P. (Microelectron. Eng., 2005)

(untitled) - Ueda, K.; Yoshimura, M. (Thin Solid Films, 2004)

(untitled) - Biesuz, M.; Bortolotti, M.; Tessarolo, F.; Canteri, R.; Giopato, P.; Nollo, G.; Chiappini, A.; Vilémová, M.; Sglavo, V. M.; Sorarù, G. D. (J. Eur. Ceram. Soc., 2022)

(untitled) - Umalas, M.; Vlassov, S.; Polyakov, B.; Dorogin, L. M.; Saar, R.; Kink, I.; Lõhmus, R.; Lõhmus, A.; Romanov, A. E. (J. Cryst. Growth, 2015)

Proceedings of SPIE vol. 10453 - Sniķeris, J.; Gerbreders, V. (Direct formation of nanostructures by focused electron beam on a surface of thin metallic films, Third International Conference on Applications of Optics and Photonics, Faro, Portugal, 22.8.2017)

(untitled) - Snikeris, J.; Gerbreders, V.; Tamanis, E. (J. Micro/Nanopatterning, Mater., Metrol., 2021)

(untitled) - Zaitsev, S.; Shtempluck, O.; Buks, E. (Sens. Actuators, A, 2012)

(untitled) - Amiri, M.; Dadfarnia, S.; Haji Shabani, A. M.; Sadjadi, S. (J. Pharm. Biomed. Anal., 2019)

(untitled) - Li, D.; Zhang, H.; Wang, Y.; Mustonen, K.; Shang, D.; He, M. (Carbon, 2020)

(untitled) - Kuzhir, P.; Paddubskaya, A.; Bychanok, D.; Liubimau, A.; Ortona, A.; Fierro, V.; Celzard, A. (Carbon, 2021)

(untitled) - Norouzi, Z.; Mahmoudi Najafi, S. H.; Mozaffari, S. A. (Diamond Relat. Mater., 2022)

(untitled) - Villarrubia, J. S. (J. Res. Natl. Inst. Stand. Technol., 1997)